PELATIHAN ETIKA BISNIS DAN HUKUM KEPADA MAHASISWA BISNIS - Johan, Suwinto; Manurung, Sony Priya Elita (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2023)
Ethics in business has become crucial in daily economic activities. However, ethical violations still occur frequently. In principle, ethics comes from our morals as human beings with the basis of thinking what is good and what is not. Ethics is not only needed in business but also professional ethics. This training event aims to provide additional insight into the professional ethics of advocates. The training expects students to learn about business ethics, professional ethics and the consequences if they do not practice ethics. The training is conducted by means of webinars in order to reach a large number of participants. This training concludes that business ethics has a positive impact on the long-term performance of the company.